Analisis Kinerja Keuangan PT GoTo Gojek Tokopedia TBK Periode 2020 - 2024 : Pendekatan Analisis Vertikal dan Horizontal - William Christian; Ansori Ansori; Sri Retnaning Sampurnaningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe and compare the financial performance of PT GoTo Gojek Tokopedia Tbk during the period 2020–2024. The research employs a descriptive comparative method with a quantitative approach, using vertical and horizontal analyses of the company’s financial statements, including the statement of financial position, income statement, and cash flow statement. The data used in this study are secondary data obtained from the company’s published annual financial reports. The results indicate that the company’s financial structure in the early period was dominated by intangible assets and cash as a consequence of the merger and aggressive business expansion strategy. In subsequent periods, a decline in the proportion of cash and adjustments to the value of intangible assets reflect a strategic shift toward efficiency and financial stabilization. The income statement analysis shows that the company continues to record net losses, although there is an improvement in the cost structure in the later period. Meanwhile, the cash flow analysis reveals that operating cash flows have not yet fully stabilized but exhibit a gradual improvement along with reduced reliance on external financing. Overall, the findings suggest that PT GoTo Gojek Tokopedia Tbk is undergoing a transition from an aggressive growth strategy toward enhanced efficiency and sustainable financial performance.